Evaluation of a Context-Aware Application for Mobile Robot Control Mediated by Physiological Data: The ToBITas Case Study - Gamecho, Borja; Guerreiro, José; Alves, Ana Priscila; Lourenço, André; da Silva, Hugo Plácido; Gardeazabal, Luis; Abascal, Julio; Fred, Ana (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
We present the ToBITas mobile Context-Aware application to control a mobile robot using electromyographic and accelerometric signals acquired from the user’s right-hand arm. The signals are acquired by means of an off-the-shelf low-cost device called BITalino and are processed by an Android smartphone. Our work was developed as a case study to validate the quality of the mobile applications created with a rapid-prototyping framework called MobileBIT. We evaluated the application with thirteen participants and the results suggest that participants were able to adapt to the proposed control mode, completing the task in a suitable time.